Working Materials Relating to the Weekly Political Programs ''Drót'' and ''Drótháló''
The sister TV news programs Drót (“Wire”, February-August 1994) and Drótháló (“Network”, April-June 1994) were launched in response to the Hungarian government’s media policy of the time, and were intended to bring balance to media coverage of the 1994 general election campaigns at the height of the first “media war”, the struggle for control of media output and content. Drót and Drótháló primarily covered the election campaigns, and also addressed current topics of the day, including compensation vouchers and their illegal trade, the privatization of former state-owned land and industries, and everyday difficulties experienced by small entrepreneurs and the unemployed. The programs were produced by Rexfilm, with György Baló as editor-in-chief, and Judit Kóthy, Vera Pécsi, Gábor Erdős and Pál Sipos, Zsuzsa Énekes and István Végh as editors. Both programs were made along semi-samizdat lines, produced in a small studio owned by Rexfilm executive and former television producer Ákos Róbert, and distributed on VHS cassettes by motorbike messengers to local channels all over the country by TV4. All the journalists who worked on the Drót/Drótháló programs had previously worked for MTV Hungarian Television until September 1993, when they were fired for protesting against leadership decisions. The series includes all the Drótháló programs, about 20 of the Drót programs and nearly 300 cassettes of raw material, plus two archival boxes of textual documents (transcripts of interviews, program timetables). Accruals expected